Complaints Handling and Vigilance Reporting for Stryker Neurovascular Products - Nisa, Hinan (My University, 2022)
The main goal of the company is to offer its customers the best quality products possible. One of the best ways to monitor the quality of product and provide feedback to the design, manufacturing, technical support, sales, and marketing teams is a well-designed Complaint Handling System. Medical device companies can continuously enhance user safety, regulatory compliance, and customer satisfaction by using an efficient complaint handling system. There are comprehensive quality management system software’s available to automate functions such as recording customer complaints, investigations, and adverse event reporting according to regulatory standards. Trackwise is one such software which is used by Stryker for the Complaints Handling process. Medical device companies are required by the FDA to report incidents involving medical equipment in order to detect and address problems in a timely manner. Despite the best planning of medical devices, sometimes adverse events occur. These events may include medical device malfunctions, serious injuries, and deaths. Similar way events are captured by other medical device industries and reported to FDA. The data is readily available in public database forum. The data is extracted for market analysis and is documented in periodic safety update report (PSUR) along with other requirements. Furthermore, this project also focuses on the establishment of an automated statistical tool for estimating the product usage in the field. Stryker's complaint handling system, Trackwise, serves as a central location for all complaints and supporting data. In the complaint handling team various roles are allocated to manage complaints, such as CIC (Complaint Intake Center), CMC (Complaint Management Center), and PAC (Product Assessment Center). This project focuses on CMC. After the CIC intake, CMC manages the complaint and uploads it to Trackwise. Additional event information is received via the RAQA or Sales Representative. Files an eMDR for Reportable Complaints, submit Complaints, approve Complaints after PAC investigation, and closes Complaints. The Periodic Safety Update Report is a periodic report that medical device manufacturers are required to maintain and submit to their Notified Body (NB) on a regular basis. The PSUR is a summary of the findings of Post Market Surveillance activities, as well as the conclusions reached by manufacturers for Class IIa, IIb and III devices. A description and justification for any corrective or preventative actions (CAPAs) made by the manufacturer must also be included in xviii this report. Present study encompasses the retrieval, collection and analysis of data for periodic safety update report of medical device Catheter. Stryker Neurovascular does not have an established statistical method to estimate product consumption in the market, when a product change has been made and a mixture of new and old product are in circulation. This project focuses on establishing a tool for estimating product usage in the field based on available data that eliminates the need for ad-hoc, manual analyses.
Keywords: Complaints handling; Vigilance Reporting; Periodic Safety